PENGARUH TRANSPARANSI INFORMASI PENINDAKAN OLEH PEMERINTAH KOTA TERHADAP KELUHAN (STUDI PADA TINGKAT PARTISPASI PENGGUNAAN SMARTCITY CLUE KOTA DKI JAKARTA) - Radityo Muhammad; Razie Razak (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2019)
At this time the communication channel containing the platform is being used by the people in DKI Jakarta. Therefore, the DKI Jakarta Regional Government provides a smartcity platform to facilitate the participants. With this channel communication will occur from citizens to the government. Research tries to analyze the enthusiasm of citizens in reporting cities by measuring the residents' sensitivity. Itensity measurement uses scientific data methodology that is by using big data to see human behavior. The researcher found more information about the repression of the citizen report then higher reported to the citizens. The response that was fast after being presented was one of the triggers for residents who repeatedly reported.